Residential or activity space walkability: What drives transportation physical activity?. (December 2017) - Howell, Nicholas A.; Farber, Steven; Widener, Michael J.; Booth, Gillian L.
Abstract: Background: The walkability of an individual's neighbourhood of residence is positively associated with their participation in physical activity. Reported associations between walkability and physical activity, however, are highly variable. One explanation is that many studies only assess individuals' home environments and do not account for their exposure to other areas, potentially introducing bias into observed relationships. Aim: To assess how associations between walkability and transportation physical activity (TPA) vary when walkability is defined using residential versus activity space environments. Methods: University students attending schools in Toronto, Canada were sampled as part of the StudentMoveTO survey. Participants reported a one-day travel diary accounting for all trips taken over the previous 24 h. Transportation physical activity was defined as reporting any walking or cycling trips. Walkability (quintiles, Q5 highest, Q1 lowest) was assessed using a previously validated index shown to be associated with physical activity, obesity, and diabetes. Three definitions of individuals' walkability exposure were used: (i) residential (neighbourhood around individuals' homes), (ii) full activity space (average of all locations visited), (iii) restricted activity space (average of all home, work, school locations visited). Logistic regression was used to assess the adjusted association between walkability and physical activity. Results: A total of 12, 152 individuals were included in the analyses (median (IQR) age = 21.0 (19–25), 66.9% female). Associations between walkability and TPA were significant for all definitions, but varied in magnitude, with residential walkability exhibiting the weakest association (Q5 vs. Q1 OR = 2.07 (95% CI: 1.70, 2.52)), compared with full (Q5 vs. Q1. OR = 6.54, (4.92, 8.84)) and restricted (Q5 vs. Q1 OR = 4.84, (3.76, 6.29)) activity space definitions. Conclusion: Full activity space walkability showed the strongest association with TPA, compared with more restricted definitions. Exposure misclassification may contribute to the variability in built environment & health relationships. Highlights: Residentially defined and activity space walkability exposures only modestly correlated. Using activity space walkability increased associations with activity by ~2–3 times. Home and non-home walkability were both independently associated with activity.